Pelaporan Informasi Publik : Transparansi dan Akuntabilitas - Jusra Tampubolon; Hengki Mangiring Parulian Simarmata; Demak Claudia Yosephine Simanjuntak; Sabar Duma Sihombing; Elfina Okto Posmaida Damanik; Doris Yolanda Saragih (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Public information disclosure is an important element in good governance, especially in increasing transparency and accountability of state institutions. The North Sumatra Election Agency (Bawaslu) has a strategic role in ensuring the disclosure of information related to election supervision. This community service activity was carried out to increase the understanding of Bawaslu members in the North Sumatra region in reporting information on the results of Bawaslu activities in the supervision of the 2024 elections. The method used is seminars and questions and answers about regulations and best practices in conveying information to the public involving academics and practitioners. The results of this activity showed an increase in participants' understanding of good information management and the application of accountability principles in the preparation of reports. With this activity, it is hoped that Bawaslu members can implement better reporting standards to increase public trust in election supervisory institutions.